2023
DOI: 10.1186/s40793-023-00486-w
|View full text |Cite
|
Sign up to set email alerts
|

Testing the stress gradient hypothesis in soil bacterial communities associated with vegetation belts in the Andean Atacama Desert

Abstract: Background Soil microorganisms are in constant interaction with plants, and these interactions shape the composition of soil bacterial communities by modifying their environment. However, little is known about the relationship between microorganisms and native plants present in extreme environments that are not affected by human intervention. Using high-throughput sequencing in combination with random forest and co-occurrence network analyses, we compared soil bacterial communities inhabiting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 119 publications
0
4
0
Order By: Relevance
“…In this context, it was also indicated that limited nutrient and water in soils can influence the microbiome recruitment by plants, leading to the selection of specific soil bacterial communities with beneficial functions that might help plants under harsh environmental conditions [46,47]. Thus, plant roots can modulate positive and negative bacterial interactions, as observed across the altitudinal vegetation belt in the Atacama Desert by Mandakovic et al [48]. Similarly, studies on two cactus species, Myrtillocactus geometrizans and Opuntia robusta, in arid ecosystems revealed that plant compartments, plant species, site, and season played a crucial role in the assembly of the microbiota [49].…”
Section: Bacterial Communitiesmentioning
confidence: 89%
“…In this context, it was also indicated that limited nutrient and water in soils can influence the microbiome recruitment by plants, leading to the selection of specific soil bacterial communities with beneficial functions that might help plants under harsh environmental conditions [46,47]. Thus, plant roots can modulate positive and negative bacterial interactions, as observed across the altitudinal vegetation belt in the Atacama Desert by Mandakovic et al [48]. Similarly, studies on two cactus species, Myrtillocactus geometrizans and Opuntia robusta, in arid ecosystems revealed that plant compartments, plant species, site, and season played a crucial role in the assembly of the microbiota [49].…”
Section: Bacterial Communitiesmentioning
confidence: 89%
“…Wang et al, 2022), or other factors such as vegetation, plant species, soil texture, sampling effects, and ecologically neutral diversification processes (J. Li et al, 2021;Liang et al, 2011;Mandakovic et al, 2023;Rüger et al, 2023). These considerations expand our understanding of the complexities driving functional microbial community variations in oil-polluted environments.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous research on total microbial communities, this is reasonable, given that a considerable portion of soil microbial community variation cannot be explained by measured environmental variables or geographical distance (He et al., 2023; Liang et al., 2011; Ramette & Tiedje, 2007). This gap in explanation may be attributed to unmeasured environmental variables, like the type of petroleum pollutants affecting microbial genetic diversity (H. Y. Wang et al., 2022), or other factors such as vegetation, plant species, soil texture, sampling effects, and ecologically neutral diversification processes (J. Li et al., 2021; Liang et al., 2011; Mandakovic et al., 2023; Rüger et al., 2023). These considerations expand our understanding of the complexities driving functional microbial community variations in oil‐polluted environments.…”
Section: Discussionmentioning
confidence: 99%
“…For example, taxonomic analysis revealed an abrupt change between the rhizosphere and the rest of the non-rhizospheric soils of Chilean altiplanic native plants from the Andean grasslands soils [ 36 ]. In addition analysis of 21 native plant species organized into three vegetation belts in the Andes in the Atacama Desert showed that plants appears to determine plant-specific microbial community composition in the soil associated to root system and showed that bacterial communities modify their ecological interactions, in particular, their positive:negative connection ratios in the presence of plant roots [ 37 ]. Thus, spatial differentiation of TS and SS as environments must be interpreted with caution, especially in studies of bacterial community assembly processes along a soil depth gradient.…”
Section: Discussionmentioning
confidence: 99%